2017
DOI: 10.1016/j.biomaterials.2017.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblastic activation of valvular interstitial cells is modulated by spatial variations in matrix elasticity and its organization

Abstract: Valvular interstitial cells (VICs) are key regulators of the heart valve’s extracellular matrix (ECM), and upon tissue damage, quiescent VIC fibroblasts become activated to myofibroblasts. As the behavior of VICs during disease progression and wound healing is different compared to healthy tissue, we hypothesized that the organization of the matrix mechanics, which results from depositing of collagen fibers, would affect VIC phenotypic transition. Specifically, we investigated how the subcellular organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 58 publications
4
66
1
Order By: Relevance
“…We began by establishing a method for 2.5D culture within PEG‐peptide hydrogels formed with photoinitiated thiol‐ene click chemistry that previously had been utilized for 2D and 3D culture of fibroblasts, facilitating comparison of cell response amongst different geometries . These hydrogels were formed with 8‐arm norbornene‐functionalized PEG to allow tuning of modulus over a wide and relevant range for mimicking healthy to fibrotic tissues (E ∼1–5 to 5–10+ kPa for lung tissue), a thiol‐functionalized matrix metalloproteinase (MMP)‐cleavable peptide G C RDVPMS↓MRGGDR C G that degrades in response to a variety of MMPs secreted by fibroblasts, 2 mM of thiol‐functionalized collagen‐mimetic GFOGER peptide to promote cell adhesions, and a photoinitiator (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We began by establishing a method for 2.5D culture within PEG‐peptide hydrogels formed with photoinitiated thiol‐ene click chemistry that previously had been utilized for 2D and 3D culture of fibroblasts, facilitating comparison of cell response amongst different geometries . These hydrogels were formed with 8‐arm norbornene‐functionalized PEG to allow tuning of modulus over a wide and relevant range for mimicking healthy to fibrotic tissues (E ∼1–5 to 5–10+ kPa for lung tissue), a thiol‐functionalized matrix metalloproteinase (MMP)‐cleavable peptide G C RDVPMS↓MRGGDR C G that degrades in response to a variety of MMPs secreted by fibroblasts, 2 mM of thiol‐functionalized collagen‐mimetic GFOGER peptide to promote cell adhesions, and a photoinitiator (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we set out to establish an approach for comparing fibroblast activation across different culture geometries. For ease of comparison to prior work and relevance for widescale use, we selected well‐defined step growth PEG‐peptide hydrogels as the base matrix, which have been utilized for both 2D and 3D culture of fibroblasts . Utilizing the capabilities afforded by photopolymerization, we then established an approach for creating a layered hydrogel geometry with these synthetic matrices, where cells are cultured at the interface between layers to create a 2.5D culture for comparison to and as a bridge between 2D and 3D cultures (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…203 Similarly, heart valve interstitial cells display larger focal adhesions, increased stress fiber formation, and an accelerated mechanical response to spatially organized matrix stiffness, which combine to increase myofibroblast activation. 204 In total, these results highlight the effect of spatially varying substrate properties, and how one might design experiments to gain insight into the role that a disorganized ECM may play in fibrotic diseases or during injury or even how one might use biomaterials to manipulate cell function to regenerate healthy tissues in diseased microenvironments.…”
Section: Photocleavage Reactionsmentioning
confidence: 95%
“…18 Cell behavior and fate decisions also appear to depend on the spatial organization of mechanical surface patterning. 203,204 When a photomask was used to create subcellular stiffness patterns, hMSCs preferentially formed focal adhesions on stiffer islands and on the interface between stiff and soft regions. Furthermore, cells seeded on surfaces with uniformly spaced patterns were more responsive to changes in the percentage of stiff regions, compared to cells in contact with disorganized patterns.…”
Section: Photocleavage Reactionsmentioning
confidence: 99%
“…As a recent example, Ma et al leveraged photo-labile hydrogel cross-linkers to create homogeneous and heterogeneous patterns of elasticity with a 'pixel' size of 4 μm 2 and confirmed the pattern fidelity with atomic force microscopy. It was found that valvular interstitial cells cultured on gels with a heterogeneous pattern of elasticity had smaller focal adhesions, increased rates of proliferation, and decreased markers of myofibroblast activation compared to cells cultured on a homogeneous pattern [25]. Given the physiological relevance of spatially variable biophysical signals on the cell-scale, there exists a need for materials with spatiotemporal control over the viscoelastic properties so that the cellular response to local viscoelasticity can be probed.…”
Section: Introductionmentioning
confidence: 99%